Effectiveness of the power and speed dry-land training in female swimmers aged 15-16 - Guzik-Kopyto, A.; Nowakowska-Lipiec, K.; Nocon, A.; Gzik, M.; Michnik, R. (Acta of Bioengineering and Biomechanics, 2021)
Purpose: This work aimed to define the impact of the introduction of power and speed dryland training in female swimmers aged 15-16 on the rise of time results at a distance of 200m and on the increase of the strength level of the muscle groups in the elbow joint. Method: The investigations were conducted in a group of 28 junior female swimmers: group1(aged 13-14) with speed and endurance training based on "water" exercises; group 2 (aged 15-16) with extra power and speed dry-land training. The following parameters were analyzed: time results, the moments of muscle forces in the elbow joint at the extension and flexion movements in isokinetic conditions and the ratio of the values of moments of muscle forces of flexors in relation to extensors. Results: Statistically significant differences between groupswere found for the following parameters: the time results from swimming 200m with (p<0.001) and without using lower limbs (p=0.031), the ratio of the moments of muscle forces of flexors to extensors (p<0.05). Conclusions: The results of the correlation analysis show that the higher the moments of muscle forces of flexors and extensors of the elbow joint, the shorter the time obtained in swimming 200m in the freestyle stroke.